Kunstfiguren : Ästhetische Strategien und performative Praktiken von künstlerisch gestalteten Identitäten - Heim, Sibylle; Kandathil, Mira; Senkpiel, Fabiana (2024)
Lady Gaga, Jilet Ayşe, Müslüm, Andy Warhol and Sun Ra are nationally and internationally known artistic characters. This publication deals with artistically designed identities at the intersections of visual art, performance, theatre, film, cabaret, stand-up comedy and music, analysing the currently widespread but as yet rarely explored nature of such artistic characters' representation. These are fictional identities that artists create for themselves, with which they appear in various contexts and media. The contributions focus on aesthetic strategies and performative practices as well as the field of tension between the performing artist and the artistic character performed. Who are Maria Marshal, Jilet Ay¸se, Müslüm, and Soya the Cow? The representational form of artistic characters is investigated scientifically for the first time...